Cardiac scoring systems, coronary artery disease and major adverse cardiovascular events: A scoping review - Preesha Premsagar; Colleen Aldous; Tonya Esterhuizen (South African Family Practice, 2023)
Background: In 2019, the World Health Organization (WHO) declared coronary artery disease (CAD) as the leading cause of death globally for the last 20 years. Early screening and detection (primary prevention) and intervention (secondary prevention) are necessary to curb CAD and major adverse cardiovascular event (MACE) prevalence. A scoping review to assess the current literature on using cardiac scoring systems to predict CAD and MACE was performed.